(untitled) (Journal of the College of Basic Education, 2023)
Tumor associated macrophage (TAMs) are alternatively activated macrophages that enhance tumor progression by prompting tumor cell invasion ,migration and angiogenesis .The study aimed to detect of the distribution TAM bladder tumor tissues , and to clarify the relationship between the TAMs and clinicopathological grade of bladder cancer. Immunohisochemistry was used to detect CD68 as general marker for TAMs macrophage in tissue . Fifty patients with urinary bladder carcinoma and twenty benign bladder biopsies from patients with urinary bladder diseases (UBD) were included in this study . Our data showed a high positive immunohistochemical CD68 expression of UBC tumor tissues than in UBD tumor tissues (84% versus 45% ; p≤ 0.01) , also a significant difference was observed in grades among patients with UBC in CD68+ expression, high grade tumor cases showed positive immunohistochemical CD68 expression in 27(96.4%), while only 15 cases (68.2%) of low grade tumor showed positive CD68 expression . The results showed that the infiltration of CD68-positive may contribute to poor prognosis in advanced urinary bladder carcinoma